2020
DOI: 10.1021/acsbiomaterials.9b01852
|View full text |Cite
|
Sign up to set email alerts
|

MgO Nanoparticles Protect against Titanium Particle-Induced Osteolysis in a Mouse Model Because of Their Positive Immunomodulatory Effect

Abstract: Aseptic prosthetic loosening (APL) often leads to the failure of prostheses. It is inseparable from wear-particle-induced macrophage-mediated inflammatory responses and osteolysis. Mg2+ is a metal ion with excellent anti-inflammatory properties. Herein, Mg2+ was introduced into a nanomedicine (MgO nanoparticles (MNPs)) to protect against APL. MNPs could be phagocytized by macrophages and gradually degraded intracellularly. Following MNPs treatment, lipopolysaccharide (LPS)-activated macrophages polarized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…This antagonizing action on RANKL prevents osteoclast differentiation, which, in turn, may prevent bone resorption. These results are in agreement with the findings reported in earlier studies. TRAP is one of the important gene associated with osteoclast differentiation; therefore, the expression level of TRAP was studied in differentiated RAW 267.4 cells. The results revealed that both MSN and MSN-SH caused reduction in the expression levels of TRAP, as evident in the figure. Thus, MSN-SH promotes osteogenesis by upregulating the osteogenic genes, such as ALP, RUNX-2, OCN, and OPN and, at the same time, by inhibiting osteoclastogenesis by downregulating osteoclastic gene expression, such as RANKL and TRAP.…”
Section: Resultssupporting
confidence: 91%
“…This antagonizing action on RANKL prevents osteoclast differentiation, which, in turn, may prevent bone resorption. These results are in agreement with the findings reported in earlier studies. TRAP is one of the important gene associated with osteoclast differentiation; therefore, the expression level of TRAP was studied in differentiated RAW 267.4 cells. The results revealed that both MSN and MSN-SH caused reduction in the expression levels of TRAP, as evident in the figure. Thus, MSN-SH promotes osteogenesis by upregulating the osteogenic genes, such as ALP, RUNX-2, OCN, and OPN and, at the same time, by inhibiting osteoclastogenesis by downregulating osteoclastic gene expression, such as RANKL and TRAP.…”
Section: Resultssupporting
confidence: 91%
“…Implant-based particle debris, including UHMWPE, elicits a systemic immunological response and attracts monocytic cells to phagocytoze granules, resulting in the induction of ROS stress and augmented the secretion of pro-inflammatory cytokines, including TNF-α, IL-1, IL-6, and IL-8, all of which make a significant participation to osteolysis [ 80 ]. Oxidative stress caused by ROS is one of the factors that cause osteoclasts to accelerate bone resorption [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…As cells of innate immunity, macrophages are among the first batch of cells recruited to biomaterial surface after the implantation surgery. The high plasticity of macrophages allows them to switch their functions from one to another under various kinds of stimuli such as biomaterial surface characteristics, bioactive inorganic ions and immuno-modulatory biomolecules [11][12][13]. According to the surface markers and functions, macrophages could be roughly classified as pro-inflammatory M1 and anti-inflammatory M2 phenotypes [14].…”
Section: Introductionmentioning
confidence: 99%